Faith in Humanity: Religious Charitable Organizations Solidarity towards Migrants in the United Arab Emirates - Wafa Barhoumi Hamdi; Semiyu Adejare Aderibigbe; Mesut Idriz; Mouza Mohamed Alghfeli (Religions, 2024)
The plight of migrants and the need to foster their integration into diverse societies are of concern to global communities, governments, and charitable organizations. This study explored the roles of philanthropic organizations in the United Arab Emirates (UAE) in demonstrating solidarity towards migrants, exploring the multifaceted dimensions of compassion and support rooted in diverse religious principles. The study adopted a qualitative approach guided by the interpretivist paradigm when collecting and analyzing data. From its findings, the study highlights the integral role they play in addressing the complex needs of migrant communities. For instance, they provide food and financial support in clearing hospitals, tuition, and rent bills. In addition, the findings show that the organizations identify migrants in need through their open-door policy, encouraging those in need of support to contact them directly, with collaboration also being essential for the effectiveness of their services. By affirming the positive contributions of religious charities, this study underscores their role in promoting the well-being and social cohesion of migrants, ultimately exemplifying a shared commitment to humanitarian values and reinstating faith in the collective capacity for compassion and solidarity.